Electricity demand and carbon emission in power generation under high penetration of electric vehicles. A European Union perspective. (November 2020) - Gryparis, Emmanouil; Papadopoulos, Perikles; Leligou, Hellen C.; Psomopoulos, Constantinos S.
Abstract: The European Union has set targets to reduce the greenhouse gases emissions in total energy consumption as a part of the securing the clean energy initiative and the efforts of carbon emissions reductions of 90%, compared to the 1990 ones, until 2050. The transport sector is particularly exacerbating the above problems. Focusing on their fight, European authorities have invested and continue to invest in electric propulsion. In the European Union, electric mobility has grown tremendously in the last decade. Specifically, more and more automobile industries are turning their interest in electric technology to replace conventional cars which they use internal combustion engine. This study tries to evaluate the impact of the electric vehicle penetration in the electricity demand and related emissions inside the EU, in three steps. First, the penetration of electric vehicles into the Union is evaluated through literature review, then the impact in electricity demand due to the electric vehicles penetration is estimated and finally the emission of carbon dioxide gases allocated to these changes in the electricity demand are calculated based on official data published by EuroStat. The results were calculated using the most common prognostic tools in order to identify the expected trends, and showed that the future electrification in transportation will support the efforts on reducing the carbon emissions but not that fast as it was expected as the electricity generation in EU is still based in fossil fuels at significant percentage. Highlights: The penetration of EVs' impact in electricity grids is evaluated using 2 methods. The model considers electricity consumption & number of EVs & grid characteristics. Proposed multi-parametric model uses grid losses & carbon intensity of generation. Results show that high penetration of EVs results to increased electricity demand. If demand is RES electricity then 100% EVs will decrease tremendously GHG emissions.